Occurrence of Phytophthora multivora and Phytophthora plurivora in the Czech Republic - Marcela Mrázková; Karel Černý; Michal Tomšovský; Veronika Strnadová; Božena Gregorová; Vladimír Holub; Matěj Pánek; Ludmila Havrdová; Markéta Hejná (Plant Protection Science, 2013)
Beginning in 2006, a survey of two related Phytophthora species, P. multivora and P. plurivora, was performed in the Czech Republic. Both pathogens were distributed throughout a broad range of environments including forest and riparian stands and probably became naturalised in the country. The two species differed in their frequency and elevational distribution. P. multivora was less frequent, but commonly occurred in the lowest regions such as Central Bohemia and South Moravia, i.e. areas which generally exhibit a high level of invasion. This species was isolated primarily from Quercus robur and found to be involved in oak decline. Moreover it poses a high risk to other forest trees. P. plurivora was distributed in a broad range of elevations over the entire area. A substrate specificity was detected in P. plurivora - the isolates from forest trees were more aggressive to such trees than the isolates from ericaceous ornamental plants.